Are the current balance screening tests in dance medicine specific enough for tracking the effectiveness of balance-related injury rehabilitation in dancers?: A scoping review - Ani, K. U.; Ibikunle, P. O.; Nwosu, C. C.; Ani, N. C. (Journal of Dance Medicine & Science, 2021)
Aims This review sought to determine the extent to which balance screening tests in dance medicine are representative of dance movements and to determine if such tests can be used to empirically track the effectiveness of balance-related injury rehabilitations in dancers.